To the freemen of the colony of Rhode-Island : Gentlemen, Permit me, in this public manner, to return you my grateful thanks, for the truly honourable testimony you have given me, at several successive elections, of your approval of my administration, as chief magistrate of this colony - Wanton, Joseph, 1705-1780 ([Printed by Solomon Southwick], 1775)
April 12, 1775 letter to the freemen of Rhode Island by Governor J. Wanton, in which he defended himself from claims that he was "unfriendly" to the colony's charter rights and an enemy.